Analisis Perbandingan Metode Dempster Shafer Dan Certainty Factor Dalam Mendeteksi Penyakit Anemia - Umniy Salamah; Richi Ramadhan (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
Anemia is one of the nutritional disorders that are still often found in Indonesia. The Household Health Survey found that around 57% of Indonesian adolescent girls aged 10-14 years and 39.5% of women aged 15 years and over still suffer from anemia. From the high cases of anemia sufferers, researchers aim to help the community in preventing and treating patients by providing information related to the symptoms of anemia, so that researchers will create an expert system that can diagnose anemia. An expert system is a computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that can usually only be solved by an expert in a particular field. The purpose of developing expert systems is actually not to replace the role of humans, but to transfer human knowledge into the form of systems, so that they can be used by many people and are not limited by time. In this study, researchers want to build an expert system that can detect anemia, where in this study the researcher will compare the Dempster-Shafer method and Certainty Factor, where the system is built using PHP programming language and MySQL database that can be accessed anytime and anywhere so as to make it easier for patients to diagnose anemia without the need to meet directly with experts.